2019
DOI: 10.1080/20018525.2019.1565804
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness trials: critical data to help understand how respiratory medicines really work?

Abstract: Most of the information about the benefits, safety aspects, and cost effectiveness of pharmacological treatment in the respiratory field has been obtained from traditional efficacy studies, such as randomised controlled trials (RCT). The highly controlled environment of an RCT does not always reflect everyday practice. The collection, analysis, and application of effectiveness data to generate Real World Evidence (RWE) through pragmatic trials or observational studies therefore has the potential to improve dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…36 Other RCTs examining the effect of betablockers in COPD are ongoing and positive result from these trials would have the potential to bring a valuable yet inexpensive tool to the COPD treatment arsenal. 37 The need for such RCTs is highlighted by the fact that fears of prescribing beta-blockers to COPD patients still exist. 35 Studies indicate that ASA might play a protective role in COPD, regardless of CVD, 14,38 though no RCTs assessing the issue are currently available.…”
Section: Discussionmentioning
confidence: 99%
“…36 Other RCTs examining the effect of betablockers in COPD are ongoing and positive result from these trials would have the potential to bring a valuable yet inexpensive tool to the COPD treatment arsenal. 37 The need for such RCTs is highlighted by the fact that fears of prescribing beta-blockers to COPD patients still exist. 35 Studies indicate that ASA might play a protective role in COPD, regardless of CVD, 14,38 though no RCTs assessing the issue are currently available.…”
Section: Discussionmentioning
confidence: 99%
“…Effectiveness studies provide real-world context to complement conventional RCTs, as they enrol patients more representative of those prescribed treatment in routine care, do not involve dummy inhalers [ 20 ] and allow physicians and patients to prescribe and take their medication as they would in usual care settings. The Salford Lung Study demonstrated the effectiveness of once-daily FF/VI single-inhaler therapy over usual care in a COPD population [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Всем участникам лечебного процесса: регулирующим организациям, страховым компаниям, пациентам, врачам необходима надежная и достоверная информация о преимуществах, аспектах безопасности и экономической эффективности лекарственных средств, предполагающая поиск доказательств и их использование для принятия оптимального клинического решения [7]. Ядром доказательной медицины является иерархическая классификация, где систематические обзоры, метаанализы и рандомизированные клинические исследования (РКИ) обычно рассматриваются как самый высокий уровень клинических доказательств [8].…”
Section: рандомизированные клинические исследованияunclassified